Urban Thermal Comfort: Analysis of the Impact of Revitalization Reviva Centro on Urban Microclimate of Campo Grande - Ramos Goulart, Amanda (2022)
Green infrastructure is presented in several research as an urban strategy necessary to minimize the negative effects arising from the urbanization process and provide outdoor thermal comfort. The urban revitalization project “Reviva Centro”, proposes the increase of vegetation along “14 de Julho” street, located in downtown Campo Grande, Mato Grosso do Sul, Brazil. In this sense, the aim of this study is to compare two scenarios, corresponding to the previous situations and after the implementation of the urban revitalization project. To compare the scenarios, the Envi-met program was used for 3D modeling and microclimatic simulation. The program simulates climatological interactions between surfaces, plants, and atmosphere, considering four fundamental variables of urban thermal comfort (temperature, relative humidity and wind speed and direction). The analysis and visualization of the results is based on the equivalent physiological temperature (PET), that classifies outdoor human thermal comfort conditions. Based on the results of the simulations, the increase in thermal comfort was provided in relation to cold and heat. At 8 am., an air temperature increases of 6 °C, decreasing the discomfort caused by the cold. At 16 hours the comfort gain is obtained by decreasing the air temperature, with a difference of 4.98 °C, optimizing thermal comfort in the scenario that represents the state after revitalization. The results presented in this research show the benefits of urban vegetation as a strategy to balance the urban microclimate and increase comfort for pedestrians.